Analysis and Optimization of the Coupling between Air-source Heat Pump and Building in Variable Operation Conditions - Li Sihui; Gong Guangcai; Zhou Fuyu; Liu Riming (Zhileng xuebao)
Many designers simply take rated COP (coefficient of performance) and heating capacity into consideration in terms of the performance of air-source heat pumps, leading to an insufficient heating effect of heat pumps under low temperature conditions in a hot-summer and cold-winter zone. To solve this problem, this paper established three models of capacity output, energy efficiency ratio and dynamic load demand of buildings in summer and winter, and all the three models were tested in varying operation condition. Since the capacity output of heat pumps and load demand of buildings are coupled and influenced by indoor and outdoor temperature and outdoor humidity, a comprehensive analysis of factors including indoor and outdoor temperature and outdoor humidity on the heat pump performance were conducted. As a result, the paper introduced three indicators in selecting heat pumps, namely heat pump capacity output, energy efficiency ratio in the most unfavorable conditions and a stable operation conditions where the capacity output can satisfy the demand of buildings. With the operation method mentioned above, the actual performance of the selected heat pumps and the degree to which they satisfy the building load demand can be effectively predicted. Meanwhile, the selection method and evaluation standard of air-source heat pump can be greatly improved.